PHENOLOGY AND YIELD OF CORIANDER AS INFLUENCED BY SOWING DATES AND IRRIGATION - A. B. SHARANGI,; A. ROYCHOWDHURY, (The Bioscan, 2014)
Effect of 3 irrigations viz., 15 + 30 + 45 + 60 + 75 + 90 + 105 DAS + seed set (I1), 15 + 30 + 45 + 60 DAS + seed set (I2), 15 + 30 DAS + seed set (I3) alongwith 6 sowing dates viz., 5th,12th,19th, 26th November, 3rd and 10th December were studied on coriander based on a RBD with 3 replications in HRS, Mondouri, BCKV, India. A delay in sowing from November 5 to December 10 decreased growth and influenced phenology. November 5 exhibited significant improvement in yield attributes namely umbel and umbellets plant-1(25.58 and 6.85), seeds umbel-1 (30.55), test weight(12.61 g), seed weight plant-1 (6.85 g), essential oil (o.25%-0.33%) and yield hectare-1(1098.33 kg ha-1). Similarly irrigation influenced plant height at 60 DAS (19.45 cm - 25.28 cm), 90 DAS (64.26 - 76.93 cm) and harvesting (80.16 cm- 97.59 cm), number of primary branches (6.69-7.37), 50% germination (10.28-11.03 days), flower initiation (60.19-63.94 days), 50% flowering (71.56-75.06 days) and fruit maturity(127.61-139.44 days). It can be concluded that the optimum date of sowing viz.5th November along with irrigation level viz.I1 showed best results for important growth parameters and all yield attributes and quality characters of coriander.